Domain selective labeling for NMR studies of multidomain proteins by domain ligation using highly active sortase A - Aizu, Takahiro; Suzuki, Takumi; Kido, Akihiro; Nagai, Kan; Kobayashi, Ayaho; Sugiura, Reiko; Ito, Yutaka; Mishima, Masaki (Biochimica et biophysica acta. General subjects, 2020)
Structural study of multidomain proteins using NMR is an emerging issue for understanding biological functions. To this end, domain-specific labeling is expected to be a key technology for facilitating the NMR-assignment process and for collecting distance information via spin labeling. To obtain domain-specific labeled samples, use of sortase A as a protein ligation tool is a viable approach. Sortase A enables ligation of separately expressed proteins (domains) through the Leu-Pro-X-Thr-Gly linker. However, the ligation reaction mediated by sortase A is not efficient. Poor yield and long reaction times hamper large-scale preparation using sortase A. Here we report the application of highly active sortases to NMR analyses. Optimal yields can be achieved within several hours when the ligation reaction are mediated by highly active sortases at 4 °C. We propose that this protocol can contribute to structural analyses of multidomain proteins by NMR. •Protein-protein ligation was achieved within several hours at 4 °C using highly active sortases.•Enough yield at 4 °C ligation using highly active sortases is favored for a wide variety of proteins.•Highly active sortases are shown to be useful for domain specific labeling for NMR studies.